2018
DOI: 10.1038/s41598-018-19732-0
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidative, anti-inflammatory and anti-apoptotic effects of ellagic acid in liver and brain of rats treated by D-galactose

Abstract: Accumulating evidence has suggested that oxidative stress and apoptosis are involved in the ageing process. D-galactose (gal) has been reported to cause symptoms of ageing in rats, accompanied by liver and brain injuries. Our study aimed to investigate the potential antioxidative, anti-inflammatory and anti-apoptotic effects of ellagic acid and to explore how these effects act on rats in a D-gal-induced ageing model. Ageing was induced by subcutaneous injection of D-gal (100 mg/kg/d for 8 weeks). Ellagic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
104
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 57 publications
18
104
0
Order By: Relevance
“…which was the main cause of many types of organ damages. Previous studies also showed that mitochondrial ROS induced the activation of a large number of mitochondrial apoptotic proteins, leading to the cellular apoptosis and organ damages (Chen et al, 2018). d-galactoseinduced aging mouse's liver and brain hippocampi were more susceptible to be injured (Rathod, Kale, & Joshi, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…which was the main cause of many types of organ damages. Previous studies also showed that mitochondrial ROS induced the activation of a large number of mitochondrial apoptotic proteins, leading to the cellular apoptosis and organ damages (Chen et al, 2018). d-galactoseinduced aging mouse's liver and brain hippocampi were more susceptible to be injured (Rathod, Kale, & Joshi, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…In our study, we aimed to demonstrate that during a period of 8 weeks of aging model establishment via subcutaneous injection of d ‐gal in mice, WSC and WS could protect against d ‐gal‐induced organ injury in vivo. Studies showed that mice subcutaneously injected the d ‐gal neck exhibited a significant memory loss, body weight declined, and organ index reduced (Baeta‐Corral et al., ; Chen et al., ; Zhang et al., ). In present studies, it had been clearly demonstrated that the administration of d ‐gal had caused the atrophy of the brain, thymus, and liver, while no significant changes were found on spleen and hear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that blocking or inhibiting IL‐1β can significantly lower the risk of chronic diseases (Dinarello, Simon, Jos, & van der Meer, ). Also, ellagic acid, a compound identified in blackberry seed flour extract (Table ), has been reported for its anti‐inflammatory capacity (Chen, Chen, & Zhou, ; El‐Shitany, El‐Bastawissy, & El‐desoky, ). The mechanism of action for ellagic acid's anti‐inflammatory capacity is still not clear.…”
Section: Resultsmentioning
confidence: 99%